Thallium Poisoning - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Four young adults poisoned with thallium contained in maliciously contaminated marzipan ball candy are reported from the New York City Poison Center, and East Carolina University School of Medicine, Greenville, NC.